(untitled) (Islamic Sciences Journal, 2023)
All praise is due to Allah. Who graces good deeds, and peace upon the prophet who is the seal and to whom has been sealed al messages, and peace upon all his companions and those who follow them till judgment day and after in : This paper deals with collecting and directing the correct Quranic readings in (Albaidawi’s explanation which is called: Anwar Altanzeel wa Asrar Altaweel), the second half from Surat Al-maada, I followed the way in which I study in details. That has been achieved by following Alemam Albaidawi’s speeches in narrating verses in which the correct Quranic readings are mentioned, collecting and directing , the analytical method deals with studying the verses in which the correct Quranic readings are mentioned , and verifying them by multiple reading books and directing them by depending on book of protests , reasons, linguistics , morphology and etc . then dividing verses in which the correct Quranic readings are mentioned into paragraphs, and number the verse which one wants to search for or look for.